사물인터넷의 경량 IP 카메라 취약점을 이용한 해킹 공격 및 대응 방안 - 조이든(Eden Cho); 박수진(Soojin Park); 강남희(Namhi Kang) (디지털콘텐츠학회논문지, 2019)
사물인터넷(IoT: Internet of Thing) 기술은 사용자 주변의 일상 사물들이 상호 연결되어 정보를 공유할 수 있도록 해준다. 이러한 혁신적인 기술은 인간의 삶에 긍정적인 변화를 가져올 수 있다. 그러나 적절한 보안 기술이 적용되지 않으면 민감한 개인 정보가 인터넷에 공개 될 수 있다. IoT 환경에서 보안은 민감한 개인 정보 유출뿐만 아니라 생명에 직결된 문제가 발생 할 수 있기 때문에 반드시 지원되어야 하는 핵심 기술이다. 본 논문에서는 IoT 장치(IP 카메라를 예로 적용)에 대한 해킹 공격을 수행하여 IoT 경량 장치는 여러 가지 잠재적인 취약성을 가지고 있기 때문에 안전하지 않다는 사실을 보인다. 해킹 테스트에서 공격자는 쇼단(Shodan) 검색 엔진을 사용하여 대상 IP 카메라를 발견하고, 대상 장치의 비디오 데이터를 훔칠 수 있다. 또한 공격 대상 장치의 동작을 강제로 종료(즉, 서비스 거부 공격 수행)시킬 수 있다. 본 논문은 시험을 통해 분석된 잠재적 보안 위협을 분석하여 각 공격들에 대처할 수 있는 방안들을 제시한다. The IoT(Internet of things) technology enable various daily-life objects around user to be connected with each other for sharing information. Such an innovative technology can lead to positive changes in human life. However, if there is no proper security mechanism, private and sensitive data around human can be revealed to public Internet. To support security is the mandatory requirement in IoT services because it is related to the disclosure of private information but also directly related to the human safety. In this paper, we perform hacking attacks against an IoT device (IP Camera as an example) to show that such an lightweight IoT device is not secure because it has several potential vulnerabilities. In the hacking scenario, an attacker can discover the target IP camera by utilizing the Shodan search engine, then he can steal private video data from the target device. Further he forcibly terminate the operation of the target device (i.e. denial of service attack). In addition, this paper describes potential security threats analyzed through attacking test and suggests several countermeasures to cope with the attacks. KCI Citation Count: 4